Does the exclusion of meiofauna affect the estimation of biotic indices using stream invertebrates? - Mbaka, John Gichimu; M’Erimba, Charles M; Karanja, Henry T; Mathooko, Jude M; Mwaniki, Mercy W (Taylor & Francis, 2016)
Biomonitoring of rivers is usually undertaken using information based on macroinvertebrate assemblages. However, exclusion of meiofauna (i.e. invertebrates less than 0.5 mm in size) when sorting benthic invertebrates can affect the estimation of densities and other biotic indices. In the present study, the effect of excluding the less than 0.5 mm fraction of invertebrates on estimation of benthic invertebrate indices was investigated in the Naro Moru River, Kenya. The Shannon–Wiener diversity index, Pielou’s evenness index, a multimetric index, Simpson’s diversity index, Margalef’s diversity index, mean invertebrate density, taxa richness, and Ephemeroptera, Plecoptera and Trichoptera (EPT) densities were determined. Only mean invertebrate and EPT densities differed significantly between the greater than 0.5 mm and total fractions. In conclusion, exclusion of meiofauna from invertebrate samples can affect the estimation of some stream invertebrate biotic indices.
Keywords: Biomonitoring; Kenya; Macroinvertebrate; River; Sieve mesh size